PERAN DPRD KOTA PEMATANGSIANTAR DALAM MENYIKAPI AKSI DEMONSTRASI :STUDI DEMOKRASI PARTISIPATIF - SAHRONY SAHRONY SIAHAAN; HAPOSAN HAPOSAN SIALLAGAN (Judge : Jurnal Hukum, 2025)
The Regional People's Representative Council (DPRD) holds and performs key functions in budgeting, legislation, and oversight. The primary challenge lies in how the DPRD can establish an effective working mechanism to optimize its performance. Fostering awareness among DPRD members regarding their roles and responsibilities has become an urgent necessity, as the public holds high expectations for the DPRD to fulfill its parliamentary functions in a more tangible and impactful manner. This implies that the implementation of local governance must adhere to principles of public accountability, which in turn necessitates a strong supervisory function. This study explores the role of the DPRD of Pematangsiantar City in responding to demonstrations as part of the dynamics of participatory democracy. The aim is to investigate how the DPRD addresses demands and aspirations expressed through demonstrations, and to assess the effectiveness of the DPRD in accommodating and following up on public concerns raised through these mass actions. The findings indicate that the DPRD of Pematangsiantar City plays a strategic role in receiving and channeling public aspirations through demonstrations, while striving to maintain a balance between public interests and social stability. Participatory democracy serves as a crucial foundation in decision-making processes, where dialogue and negotiation are essential in achieving equilibrium between the DPRD, the government, and elements of civil society, including community organizations, labor unions, and students. This study highlights the importance of the DPRD's role as a facilitator in bridging communication between the government and the citizens, thereby ensuring that local policies formulated are more responsive and inclusive.